PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY DISERTAI SCAFFOLDING PROMPTING QUESTIONING TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI GERAK LURUS DI SMA - Yessi Gusmardin; Singgih Bektiarso; Iwan Wicaksono (FKIP Universitas Jember, 2019)
AbstractThe guided inquiry learning model accompanied by scaffolding prompting questioning is learning that directs the learning process in problem solving and makes students active in solving problems through instructions from scaffolding. The purpose of this research was to examine the effect of guided inquiry learning models accompanied by scaffolding prompting questioning of students' science process skills for straight-motion material in high school. This type of research an experimental research conducted at Senior High School Pakusari in the X grade students in the even semester 2018/2019 academic year. Data collection techniques used in the research were documentation and tests. Data analysis using the independent sample t-test test with the help of SPSS 23. The results of the research showed that there was significant differences between the science process skills of students in the experimental class and the control class. The conclusion of this research was guided inquiry learning model accompanied by scaffolding prompting questioning has a significant effect on students' science process skills in physics learning for straight-motion material in high school.Key word: guided inquiry, scaffolding prompting questioning, science process skills.